Post-acute phase and sequelae management of epidermal necrolysis: an international, multidisciplinary DELPHI-based consensus - S. Ingen-Housz-Oro; V. Schmidt; M. M. Ameri; R. Abe; A. Brassard; A. Mostaghimi; A. S. Paller; A. Romano; B. Didona; B. H. Kaffenberger; B. Ben Said; B. Y. H. Thong; et al. (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Long-term sequelae are frequent and often disabling after epidermal necrolysis (Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN)). However, consensus on the modalities of management of these sequelae is lacking. Objectives We conducted an international multicentric DELPHI exercise to establish a multidisciplinary expert consensus to standardize recommendations regarding management of SJS/TEN sequelae. Methods Participants were sent a survey via the online tool “Survey Monkey” consisting of 54 statements organized into 8 topics: general recommendations, professionals involved, skin, oral mucosa and teeth, eyes, genital area, mental health, and allergy workup. Participants evaluated the level of appropriateness of each statement on a scale of 1 (extremely inappropriate) to 9 (extremely appropriate). Results were analyzed according to the RAND/UCLA Appropriateness Method. Results Fifty-two healthcare professionals participated. After the first round, a consensus was obtained for 100% of 54 initially proposed statements (disagreement index < 1). Among them, 50 statements were agreed upon as ‘appropriate’; four statements were considered ‘uncertain’, and ultimately finally discarded. Conclusions Our DELPHI-based expert consensus should help guide physicians in conducting a prolonged multidisciplinary follow-up of sequelae in SJS-TEN.